The Effect of Organizational Citizenship Behavior, Individual Competence and Individual Characteristics on Employee Performance - Ryani Dhyan Parashakti; Muhamad Ekhsan; Siti Komariah (Journal of Business, Management, & Accounting, 2021)
This study aims to analyze the effect of Organizational Citizen Behavior, individual competence, and individual characteristics on the performance of employees of PT. Orizon Global Partner. The population in this study was 52 employees of PT. Orizon Global Partner. The sample used is as many as 52 employees, calculated based on the saturated sample. The sampling method used was convenience sampling. Methods of data collection using survey methods, with the research instrument is a questionnaire. Data analysis method using Partial Least Square. This study proves that Organizational Citizen Behavior has a positive and significant effect on employee performance, individual competence has a positive and significant effect on employee performance